Mathematical creative thinking ability in online learning during the Covid-19 Pandemic: A systematic review - Suherman, Suherman; Komarudin, Komarudin; Supriadi, Nanang (CV FOUNDAE, 2021)
As a result of the increased focus on creative mathematical thinking in mathematics education during the covid-19 pandemic, there has been an increase in the need to investigate how to assess mathematical creative thinking skills in online learning environments. As a result, a systematic review was carried out to determine how mathematical creative thinking has been evaluated in the literature. We examined 124 journal articles from SCOPUS, ELSEVIER, WoS, ERIC, and SAGE to analyze specific MCT assessments from four perspectives: assessment of the familiar mathematics context, an indicator of measurement test, assessment of the unfamiliar mathematics context, and measurement test. We discovered that (a) the most familiar mathematics context for assessing mathematical creative thinking is based on students' curriculum according to their class level, and (b) indicators for assessing mathematical creative thinking frequently used open-ended questions to gather information. During this systematic review, we identified research gaps and potential future research topics to conceptualize and assess mathematical creative thinking skills while participating in online learning activities. Researchers and teachers are expected to benefit from the findings, which will aid them in determining the most effective method of teaching and assessing mathematical creative thinking